1992
DOI: 10.1177/026921559200600106
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the assessment of spasticity by the Wartenberg pendulum test and the Ashworth grading scale in patients with multiple sclerosis

Abstract: The Wartenberg pendulum test is an objective quantitative method for the assessment of muscle tone. We have compared the results of measurements of muscle tone using this method with traditional clinical assessments graded on the Ashworth scale. Two indices ( R 1 and R 2 ) were measured from the Wartenberg test. Both were related to readings from the Ashworth scale. The ratio R 2 (the ratio of the amplitude of the first swing to the difference in angle between the start and finish positions), however, showed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 6 publications
1
13
1
Order By: Relevance
“…The index correlates well with the clinical evaluation of muscle hypertonia graded on the Ashworth scale, and provides a more objective and finely graded measurement. 38 Here, mean R 2n values were averaged over the three repetitions on each side. In addition, the magnitude of total ipsilateral lower limb EMG activity generated during the pendulum test was calculated as the sum of the root mean square (RMS) of the EMG activity across the four ipsilateral muscle groups, between the onset of the maneuver, drop of leg from horizontal position, and the time when the resting angle was reached.…”
Section: Wartenberg Pendulum Testmentioning
confidence: 99%
“…The index correlates well with the clinical evaluation of muscle hypertonia graded on the Ashworth scale, and provides a more objective and finely graded measurement. 38 Here, mean R 2n values were averaged over the three repetitions on each side. In addition, the magnitude of total ipsilateral lower limb EMG activity generated during the pendulum test was calculated as the sum of the root mean square (RMS) of the EMG activity across the four ipsilateral muscle groups, between the onset of the maneuver, drop of leg from horizontal position, and the time when the resting angle was reached.…”
Section: Wartenberg Pendulum Testmentioning
confidence: 99%
“…[55][56][57][58][59] In its most simple form, the patient is seated or lying with the lower leg hanging over the end of a couch. The examiner then extends the leg to the horizontal position, while the patient is told to relax.…”
Section: Pendulum Testmentioning
confidence: 99%
“…This ratio shows a clear correlation to the severity of spasticity as evaluated by the AS. 59 The advantage of the pendulum test is its simplicity, and the more refined quantification of the severity of spasticity that is obtained compared to the AS. However, it also has several drawbacks.…”
Section: Pendulum Testmentioning
confidence: 99%
“…Different test positions have been studied in adults: lying supine (Jamshidi and Smith 1996), semi-supine , Leslie et al 1992 and sitting up (Katz et al 1992). Brown and collaborators studied the importance of the test position in non-disabled elderly individuals and found that the position contributed very little to the total variability (Brown et al 1988a).…”
Section: Individual Values and Mean Of Right (S) And Left (V) Legs Inmentioning
confidence: 99%